Gastrointestinal Cancers and Personalized Medicine - Mini, Enrico; Nobili, Stefania (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Gastrointestinal cancers, such as esophageal and gastric cancers, pancreatic cancers, hepatobiliary cancers, colorectal cancers and gastrointestinal stromal tumors, are frequently diagnosed at an advanced stage and have a dismal prognosis. Even in patients with potentially curative cancer, nearly 50% will develop recurrent disease despite aggressive treatments. A number of biomarkers currently guide treatment decisions for patients with gastrointestinal neoplasms. Major technological advances in genomics have made it possible to identify critical genetic alterations in cancer, furthering oncology along the path to "personalized cancer medicine". Future research efforts will focus on the identification of new biomarkers, moving existing biomarkers into earlier lines of therapy and evaluating new combinations of existing biomarkers and therapies.The aim of this Special Issue is to provide an overview of exciting new research in the area of gastrointestinal tumors that may establish innovative personalized management and precision medicine modalities for individualized care.